Della mente sovrana del mondo - Rossi, Tommaso (I Quaderni del Lab, 2014)
Tommaso Rossi (1673-1743), Abbot of Montefusco in the Kingdom of Naples, devoted his life to metaphysical and theological studies and had epistolary relations with Giambattista Vico. In his philosophical works "Dell'animo dell'uomo" and "Della mente sovrana del mondo", he faced the problem of human nature and of the nature of God's mind, crossing some key-questions in the philosophy of modern age, such as the mind-body relation, the possibility for the human knowledge to know the natural and divine things, and the definition of the matter. Tommaso Rossi's thought, hostile to all forms of atheism and materialism, took part in the philosophical debate which, from Locke to Descartes and Spinoza, tried to define the new field and the new role of natural science. "Della mente sovrana del mondo" (1743), whose third part is dedicated to the exam of Spinoza's philosophical system, is an important document, not only of the reception of Spinoza, but also of the philosophical redefinition for a cosmological and gnoseological order where the human wit plays a very important role.